IS-LM curve in the 2000-2020 period: Some recommendations on macroeconomic policies and digital economic development in Vietnam - KHANH, PHAM QUOC (The journal of contemporary issues in business and government, 2021)
The socio-economic development strategy for the 2021-2030 period with a vision to 2045 requires the proactive and flexible governance of the Government, especially in macroeconomic executives and digital economic development policies. The IS-LM model is one of the many approaches of economists in research to make recommendations on economic policies and governance of Governments. The following research focuses on developing and analyzing the IS-LM curve in the 2000-2020 period of Vietnam to serve as a basis for recommendations and contribute to creating a scientific basis for the macroeconomic executives of the Government. The research results help to point out recommendations related to the direction to operate monetary policy, financial policy and priorities related to sectors / areas that support digital transformation, the development of the digital economy of Vietnam in the coming years.